Emodin inhibits respiratory syncytial virus entry by interactions with fusion protein - Xiong, Yingcai; Tan, Guangxing; Tao, Keyu; Zhou, Yinghui; Li, Jun; Ou, Weiying; Shen, Cunsi; Xie, Tong; Zhang, Chao; Hou, Yayi; Ji, Jianjian (Frontiers in Microbiology, 2024)
Respiratory syncytial virus (RSV) fusion (F) protein is essential for facilitating virus entry into host cells, providing a hopeful path for combating viral diseases.However, F protein inhibitors can rapidly select for viral resistance. Thus, discovering new inhibitors of F-protein is necessary to enrich the RSV drug development pipeline.In this study, we screen 25 bioactive compounds from Chinese herbal medicines that exhibit a strong binding to the RSV-F protein using surface plasmon resonance. After screening, we found emodin could strongly bind to RSV-F protein, and could effectively curb RSV infection. Further investigations certificated that emodin specifically disrupts the attachment and internalization phases of RSV infection by targeting the RSV-F protein. In vivo studies with mice infected with RSV demonstrated that emodin effectively reduces lung pathology. This therapeutic effect is attributed to emodin's capacity to diminish pro-inflammatory cytokine production and reduce viral load in the lungs. In conclusion, our findings provide initial insights into the mechanism by which emodin counters RSV infection via engagement with the RSV-F protein, establishing it as a viable contender for the development of novel therapeutic agents aimed at RSV.